Resistance Reservoirs and Multi-Drug Resistance of Commensal Escherichia coli From Excreta and Manure Isolated in Broiler Houses With Different Flooring Designs - Chuppava, Bussarakam; Keller, Birgit; Abd El-Wahab, Amr; Sürie, Christian; Visscher, Christian (Frontiers in Microbiology, 2019)
CCarriage of resistant bacteria and spread of antimicrobial resistance (AMR) in the environment through animal manure pose a potential risk for transferring AMR from poultry and poultry products to the human population. Managing this risk is becoming one of the most important challenges in livestock farming. This study focused on monitoring the prevalence of multi-drug resistance bacteria and development of AMR depending on ﬂooring. In two experiments (2x15,000 birds), broilers were always divided in two different stables. In the control group, the entire floor pen was covered with litter material and in the experimental group, the flooring system was partly modified by installing elevated slat platforms equipped with water lines and feed pans. Over the whole fattening period, excreta and manure samples were taken (days 2, 23 and 32). In total, 828 commensal E. coli isolates were collected. The development and prevalence of resistance against four different antibiotic classes (quinolones, β-lactams, tetracyclines and sulfonamides) were examined by using broth microdilution. At the end of the trials, the amount of manure per square metre was twice as high below the elevated platforms compared to the control group. Approximately 58% of E. coli isolates from excreta showed resistance against at least one antibacterial agent at day 2. During and at the end of the fattening period, resistant E. coli isolates at least against one of the four antibacterial agents were observed in excreta (46% and 46%, respectively) and manure samples (14% and 42%, respectively), despite the absence of antibacterial agent usage. In spite of less contact to manure in the experimental group, the prevalence of resistant E. coli isolates was significantly higher. Animals preferred the elevated areas which inevitably led to a local high population density. Animal-to-animal contact seems to be more important for spreading antimicrobial resistant bacteria than contact to the litter-excreta mixture. Therefore, attractive areas in poultry housing inducing crowding of animals might foster transmission of AMR. In poultry farming, enrichment is one of the most important aims for future systems. Consequently, there is a need for keeping birds not carrying resistant bacteria at the start of life.